Study on sediment management using wall jet - Syaifudean Selamat. (2010)
This report presents the results of an extensive experimental study on the rate of scouring and scour development under different combinations of experimental parameters factors such as jet diameter, jet velocity, sediment size and thickness of sediment deposit. The minimum cleansing velocity needed to make a clearance of 1cm on the channel bed due to different heights of sand deposits and different jet diameters are also presented. Evolution of scouring development confirms with preceding research where erosion was the fastest at the start of each experiment and will ultimately approach steady state condition. The main governing factor of the scouring parameter characteristics that best correlates the maximum scour profiles was the densimetric Froude number, Fo. The relationship between scour length with time was normalized by their corresponding asymptotic value. By using the dimensionless characteristics between Ls/(Ls* ) and t/t* , the time that needed to create the preferred scouring can be calculated using the equation where the asymptotical value of the scouring parameters were already known. The critical velocity that was needed to create a clearance of 1cm on the channel bed increases exponentially with sediment height. Bigger jet diameter required lower velocity to scour a fixed sediment height compared to smaller diameter jets.